2018
DOI: 10.1038/s41598-018-23417-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor PAX6 as a novel prognostic factor and putative tumour suppressor in non-small cell lung cancer

Abstract: Lung cancer is the leading cause of cancer deaths. Novel predictive biomarkers are needed to improve treatment selection and more accurate prognostication. PAX6 is a transcription factor with a proposed tumour suppressor function. Immunohistochemical staining was performed on tissue microarrays from 335 non-small cell lung cancer (NSCLC) patients for PAX6. Multivariate analyses of clinico-pathological variables and disease-specific survival (DSS) was carried out, and phenotypic changes of two NSCLC cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…14,23 However, a previous study reported conflicting results, suggesting that PAX6 is a positive prognostic marker in NSCLC in node-positive patients. 40 These differences could be attributed to a lack of sufficient data and clarity regarding the underlying mechanism of the role of PAX6 in this disease. The current study showed that higher PAX6 expression significantly correlated with reduced duration of OS in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…14,23 However, a previous study reported conflicting results, suggesting that PAX6 is a positive prognostic marker in NSCLC in node-positive patients. 40 These differences could be attributed to a lack of sufficient data and clarity regarding the underlying mechanism of the role of PAX6 in this disease. The current study showed that higher PAX6 expression significantly correlated with reduced duration of OS in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of PAX6 as a tumor suppressor has been shown in retinoblastoma, prostate cancer, and glioblastoma cell lines. On the other hand, some oncogenic properties of PAX6 were found in colorectal adenocarcinoma, retinoblastoma, and breast tumor cell lines ( Kiselev et al, 2018 ). In the miR-383/PAX6 pathway, downregulation of miR-383 together with the upregulation of PAX6 was found in CRC tissues and cells.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Luo et al had suggested that miR-7 negatively regulates PAX6 protein levels, which can promote the proliferation and invasion of NSCLC cells via activation of the ERK and MAPK signaling pathways [16]. Kiselev et al also showed that the transcription factor PAX6 was a novel prognostic factor and putative tumor suppressor in non-small cell lung cancer [17]. Pax6 also interacts with the Smad3 MH1 domain, and Pax6/Smad3 interactions appear to be necessary for TGF-β signaling [18].…”
Section: Introductionmentioning
confidence: 99%